Challenges Related to Housing Finance in Developing Nations - Chikezirim Okorafor (Journal of Construction Project Management and Innovation, 2025)
Housing is a crucial component of developmental activities and usually necessitates funding over an extended period of time. The lack of long-term financial instruments is a significant challenge for the bulk of the population towards property acquisition. Nevertheless, in developing nations like Nigeria, the utilization of long-term loans is limited, especially among the middle class and people with lower incomes. The majority of individual in Nigeria construct their houses gradually over a period of time without long-term loans. The limited utilization of long-term loan is an indication of market deficiency and regulatory inefficiency. Against this background, the research examines the limitations that effect housing finance for real estate investors in Imo state, Nigeria. The study utilizes a questionnaire survey to collect primary data and a literature review to acquire secondary data. The primary data was analysed using descriptive statistics. The core findings indicate that the requirements are prohibitively high for the average investor. The majority of investor's primarily rely on loans for real estate finance, and there is a huge issue with bureaucratic bottlenecks in loan administration, among other factors. The study suggest that the government should enhance the capabilities of primary mortgage institutions (PMIs). Financial institutions should lower certain lending criteria such as interest rates and application procedures, and standardize repayment periods to enhance accesibility and affordability. In addition, short-term loan arrangement of commercial banks should be discouraged to pave way for long-term arrangement so that more investors can have access to housing finance.